The optimality of heterogeneous tournaments - Marc Gürtler; Oliver Gürtler (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2013)
We investigate the effect of employee heterogeneity on the incentive to put forth effort in a market-based tournament. Employers use the tournament's outcome to estimate employees' abilities and accordingly condition their wage offers. Employees put forth effort, because by doing so they increase the probability of outperforming the rival, thereby increasing their ability assessment and thus the wage offer. We demonstrate that the tournament outcome provides more information about employees' abilities in case they are heterogeneous. Thus, employees get a higher incentive to affect the tournament outcome, and employers find it optimal to hire heterogeneous contestants.
Keywords: D83; J24; J31; M51; 330; tournament; competitive labor market; heterogeneity; learning